ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP SISTEM INFORMASI AKADEMIK STEBIS IGM MENGGUNAKAN METODE PIECES FRAMEWORK - Terttiavini; Aprianita Kartini; Ahmad Sanmorino (Program Studi Ilmu Komputer FMIPA-UHO, 2024)
Academic information systems are one of the information systems most widely used by universities. Academic information systems are designed to meet the needs of universities in providing computerized educational services to improve performance, service quality, competitiveness and the quality of human resources created. The Indo Global Mandiri College of Economics and Sharia Business, known by the abbreviation STEBIS IGM, is a college that has utilized information technology by developing the STEBIS IGM Academic Information System (SIAKAD). The STEBIS IGM Academic Information System is a system that is used as a basis for students' needs to obtain information related to class schedules, filling in KRS, study results cards, student grades, student bills, transcripts of lecture results, consultations, study results and other information. The aim of this research is to determine the level of student satisfaction with the STEBIS IGM academic information system using the Pieces Framework method which consists of six (6) variables, namely Performance, Information and Data, Economic, Control and Security, Efficiency, Service. Respondents in this study were active students in the class of 2021 and class of 2022 who used the STEBIS IGM academic information system. The results that will be obtained from this research are the level of student satisfaction with the STEBIS IGM academic information system. Keywords: Academic Information System, STEBIS IGM, Satisfaction